DIVERSITY AND DISTRIBUTION OF CYANOBACTERIA IN THE CHALLENGING ENVIRONMENT OF PADDY FIELDS IN COASTAL KARNATAKA, INDIA - VEDAVYAS SHIVANAND CHAVAN; THANGADURAI DEVARAJAN (The Bioscan, 2026)
Cyanobacteria are key contributors to nutrient cycling and nitrogen fixation in paddy ecosystems. This study examined the diversity and ecological associations of coccoid cyanobacteria in relation to soil properties across the coastal districts of Karnataka, India. Soil samples from Uttara Kannada, Udupi, and Dakshina Kannada were analyzed for pH, electrical conductivity (EC), organic carbon (OC), and macronutrients (N, P, and K), while cyanobacteria were isolated and morphologically identified. A total of 46 species belonging to 20 genera were recorded, dominated by Aphanothece, Chroococcus, Merismopedia, and Gloeocapsa. Significant regional variation was observed in pH, EC, OC, N, and K, which strongly influenced diversity indices. Dakshina Kannada exhibited higher nutrient content and diversity (H′ = 3.09) than Udupi (H′ = 2.48). PCA and cluster analyses revealed strong correlations between soil nutrients and biodiversity, with Dakshina Kannada forming a distinct ecological group. Overall, soil fertility gradients regulate cyanobacterial diversity and community structure in coastal rice ecosystems, highlighting the ecological significance of native coccoid taxa in sustaining soil productivity. Keywords Cyanobacterial diversity, coccoid cyanobacteria, soil physicochemical properties, coastal paddy fields, nutrient gradients